Increased prevalence of eosinophilia in a hemodialysis population: Longitudinal and case control studies. Issue 3 (7th January 2016) - Hildebrand, Sarah; Corbett, Richard; Duncan, Neill; Ashby, Damien
Abstract: Eosinophilia is commonly found in patients with clinical reactions to the hemodialysis circuit. With modern membranes, such reactions have become less common, but they may be under diagnosed in patients with subtle symptoms, in whom the presence of eosinophilia is an important diagnostic feature. Two case reports are presented, along with a hemodialysis study of the frequency and clinical associations of eosinophilia. In three hemodialysis facilities, all current hemodialysis patients with persistent eosinophilia (greater than 1 × 10 9 /L for 3 months) were identified. Control patients without eosinophilia (less than 0.5 × 10 9 /L for 3 months) matched for age, gender, and ethnicity were identified from the same facilities. A historical cohort of patients, dialyzing at the same facilities 5 years ago, was screened for the presence of persistent eosinophilia. From 510 patients, 24 cases of persistent eosinophilia were identified (4.7%). The median eosinophil count was 1.75 × 10 9 /L (range 1.1–7.5 × 10 9 /L). The prevalence in a historical cohort 5 years previously was significantly less at 1.5% (P = 0.046). Compared to controls, patients with eosinophilia were more likely to be on an angiotensin converting enzyme inhibitor (41.7% vs. 12.5%, P = 0.049), had a lower C‐reactive protein (10 vs. 24 mg/L, P = 0.02) and were more likely to be using a fistula for access (P = 0.049). Over the following 12 months, there was no difference in the mean number of hospital admission days between cases and controls (7.6 vs. 11.5 days, P = 0.54), and no difference in mortality over 29 months (25.0% vs. 29.2%, P = 1.00). Eosinophilia remains not uncommon in hemodialysis patients, and in most cases reflects allergy to components of the dialysis circuit, which is usually subclinical. The overall prognosis for asymptomatic patients appears to be favourable.